Hypogonadism and bone health in men with HIV. Issue 11 (November 2020) - Maffezzoni, Filippo; Porcelli, Teresa; Delbarba, Andrea; Pezzaioli, Letizia Chiara; Properzi, Martina; Cappelli, Carlo; Castelli, Francesco; Quiros-Roldan, Maria Eugenia; Ferlin, Alberto
Summary: The advent of new classes of antiretroviral drugs has improved the survival of people with HIV, and several ageing-related conditions, including hypogonadism and osteoporosis, have emerged. However, both are silent conditions, and are underestimated, underdiagnosed, and not adequately treated. Several factors, including the effects of the virus, antiretroviral therapy, lifestyle factors, and comorbidities, contribute to testicular dysfunction, which in turn has important effects on bone health. The prevalence of hypogonadism is approximately 20% among men with HIV, but extreme variability in the laboratory and clinical assessment of hypogonadism is reported. The prevalence of osteoporosis is 10–30%, but the poor quality of most studies does not allow definitive conclusions on clinical management. Nonetheless, the early and detailed evaluation of gonadal function and bone health is crucial for improving the quality of life of men with HIV.